UNDERSTANDING BURNOUT AND MAJOR DEPRESSIVE DISORDER: A NARRATIVE REVIEW OF DIAGNOSTIC OVERLAP AND IMPLICATIONS - Martyna Susek; Amadeusz Furmanek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Occupational burnout and Major Depressive Disorder (MDD) share overlapping symptoms, including fatigue, sleep disturbances, cognitive impairments, and reduced motivation. Despite these similarities, burnout is primarily context-specific to occupational settings, whereas MDD affects global functioning. Differentiating the two is critical for accurate diagnosis and effective intervention. Methods: This narrative review synthesizes literature, integrating empirical studies, meta-analyses, longitudinal research, and psychometric assessments. Databases included PubMed, Frontiers in Psychology and Google Scholar. Instruments examined include the Maslach Burnout Inventory (MBI), Burnout Inventory (OLBI), Burnout Assessment Tool (BAT), PHQ-9, and HADS. Data were analyzed for symptom overlap, psychosocial and occupational determinants, neurobiological mechanisms, and clinical implications. Results: Both conditions exhibit fatigue, sleep disruption, cognitive dysfunction, and reduced motivation; however, burnout is situational, while MDD involves pervasive impairment. Chronic occupational stress may progress to MDD in vulnerable individuals. Neurobiological studies indicate shared HPA axis dysregulation, though MDD presents more systemic alterations. Psychometric analyses reveal moderate-to-strong correlations between burnout and depression measures, demonstrating partial conceptual overlap without redundancy. Additional theoretical perspectives explore whether burnout represents a subtype or prodrome of depression. Conclusions: Accurate differentiation between burnout and MDD is essential for treatment planning. Burnout may respond to organizational and environmental interventions, whereas MDD requires pharmacological and psychotherapeutic approaches. Longitudinal monitoring, multidimensional assessment, and preventive strategies are recommended to mitigate progression from burnout to depression and optimize clinical outcomes.